The association between internal governance mechanisms and internal audit function quality: evidence from Malaysia - Hadiati, Fitri (2020)
The internal audit function (IAF) quality has been recognized as an importance corporate governance mechanisms in ensuring the credibility of financial reporting, preventing fraud, and accounting scandals. This study examines the relationship between internal corporate governance mechanisms; namely audit committee attributes, board attributes, and internal audit attributes; and lAF quality. Audit committee attributes are represented by audit committee chair financial expertise, audit committee chair overlap (workload in multiple committees), audit committee size and audit committee meetings frequency; board attributes are represented by board size and board independent while internal audit attributes are represented by internal audit sourcing arrangement and internal audit investment. Ordinary least squares and logistic regressions are used to test the relationship between the variables. This study employs Malaysian Top I 00 non-financial public listed companies, based on market capitalisation in 2014. This study uses three criteria such as compliance with internal audit standards, existence of internal audit charter and adoption of risk-based internal audit plan as proxies for IAF quality. The findings reveal that audit committee chair financial expertise, audit committee chair overlap and board size have a significant influence on the overall lAF quality. In addition, audit committee chair financial expertise has a significantly positive influence on the adoption of risk-based Internal Audit plan, whereas audit committee chair overlap has a significantly negative influence on the existence of internal audit charter and compliance with internal audit standards. This study contributes to a better understanding of internal audit practices by Malaysian listed companies. The results of the study suggest that companies should improve IAF quality through internal corporate mechanisms in safeguarding their companies. This study allows policymaker to re-evaluate and reconsider adopting the original recommendation proposed in Malaysian Code on Corporate Governance 2016 pertaining to audit committee chair financial expertise